A Systematic Literature Review Protocol for the analysis of practices, measurement instruments and contextual factors inherent to Supply Chain Agility - Mohammad Hamza Alkurdi; Daniel Vázquez-Bustelo (WPOM : Working Papers on Operations Management)
Supply Chain Agility (SCA) has recently received substantial attention in the literature and in practice. The previous literature encompasses a number of different tools and constructs that are used to measure SCA, indicating the need to refine and validate a supply chain-level measurement instrument of SCA. In addition, the role of the contextual factors inherent to the implementation of SCA and the need to achieve a certain fit between SCA and other supply chain and firm strategies and orientations has received little attention by the research community. This paper represents a SLR protocol to identify definitions, practices, and measurement items of SCA, as well as the contextual factors that affect supply chain's ability to implement and measure supply chain agility. Finally, this paper will try to contribute to the theory development and advancement on SCA by clarifying the need to accomplish a certain fit between SCA and other supply chain and firm strategies and orientations.